Liquid crystalline assembly for potential combinatorial chemo–herbal drug delivery to lung cancer cells - Abdelaziz HM (Dove Medical Press, 2019)
Hadeer M Abdelaziz,1,2 Ahmed O Elzoghby,1,3–5 Maged W Helmy,1,6 Magda W Samaha,1,3 Jia-You Fang,7–9 May S Freag1,4,5,10 1Cancer Nanotechnology Research Laboratory (CNRL), Faculty of Pharmacy, Alexandria University, Alexandria 21521, Egypt; 2Department of Pharmaceutics, Faculty of Pharmacy, Damanhur University, Damanhur, Egypt; 3Department of Industrial Pharmacy, Faculty of Pharmacy, Alexandria University, Alexandria 21521, Egypt; 4Division of Engineering in Medicine, Department of Medicine, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA 02115, USA; 5Harvard-MIT Division of Health Sciences and Technology (HST), Cambridge, MA 02139, USA; 6Department of Pharmacology and Toxicology, Faculty of Pharmacy, Damanhur University, Damanhur, Egypt; 7Pharmaceutics Laboratory, Graduate Institute of Natural Products, Chang Gung University, Taoyuan 333, Taiwan; 8Research Center for Industry of Human Ecology and Research Center for Chinese Herbal Medicine, Chang Gung University of Science and Technology, Kweishan, Taoyuan 333, Taiwan; 9Department of Anesthesiology, Chang Gung Memorial Hospital, Kweishan, Taoyuan 333, Taiwan; 10Department of Pharmaceutics, Faculty of Pharmacy, Alexandria University, Alexandria 21521, Egypt Background: Lung cancer is the most common cancer and the leading cause of total deaths worldwide. Its classified into two major types including non-small cell lung carcinoma (NSCLC) and small cell lung carcinoma (SCLC) based on the origin of abnormal lung cells as well as the smoking status of the patient. NSCLC is the most common and aggressive type of lung cancer representing 80%–85% of all cases. Purpose: The aim of the study was to present lyotropic liquid crystalline nanoparticles (LCNPs) as promising carriers for co-delivery of the chemotherapeutic agent, pemetrexed (PMX) and the herbal drug, resveratrol (RSV) for effective lung cancer management.Methods: The proposed PMX-RSV-LCNPs were prepared by hydrotrope method. Hydrophobic ion pairing with cetyl trimethyl ammonium bromide (CTAB) was implemented to increase the encapsulation efficiency of the hydrophilic PMX up to 95%±3.01%.Results: The tailored PMX-RSV-LCNPs exhibited a particle size of 173±0.26 nm and biphasic release pattern with a relatively initial burst release within first 3–4 hour followed by sustained release up to 24 hours. Moreover, PMX-RSV-LCNPs manifested superior concentration and time dependent cytotoxicity profile against A549 lung cancer cells with IC50 4.0628 µg/mL. Besides, the enhanced cellular uptake profile based on bioadhesive properties of glyceryl monoolein (GMO) as well as energy independent (cholesterol dependent) pattern. In-vivo evaluations against urethane induced lung cancer bearing mice demonstrated the potentiality of PMX-RSV-LCNPs in tumor growth inhibition via inhibition of angiogenesis and induction of apoptosis. The results were supported by histopathological analysis and immunohistochemical Ki67 staining. Moreover, PMX-RSV-LCNPs displayed a promising safety profile via attenuating nephro- and hepatotoxicity. Conclusion: PMX-RSV-LCNPs elaborated in the current study hold a great promise for lung cancer treatment. Keywords: hydrophobic ion pairing, liquid crystalline nanoparticles, lung cancer, glyceryl monoolein, pemetrexed, resveratrol